ՀՊՏՀ և ՀՊՄՀ գրադարաններ - Գրիգորյան, Մայա (Հայաստանի ազգային գրադարան)
In our days, unfourtunetly, serious studies are not conducted in the library system. Each library tryes to solve its problem on its own, based on its budget and staff. In this respect, more favorable conditions are especially university libraries funded by the university system. University libraries carry out the digitization of library resources and are major trends for higher level service.
Keywords: Գրադարանագիտություն